Response of the Pacific Coast wireworm, Limonius canus, and the dusky wireworm, Agriotes obscurus (Coleoptera: Elateridae), to insecticide-treated wheat seeds in a soil bioassay - van Herk, Willem; Vernon, Robert; Moffat, Chandra; Harding, Chantelle (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2008)
Larvae of the dusky wireworm, Agriotes obscurus, and the Pacific Coast wireworm, Limonius canus, were exposed to germinated, insecticide-treated wheat seeds in a soil-filled bioassay in 2005 and 2006. Position in the bioassay and contact and/or repellence behaviour towards the seeds were recorded every 5 min for 3 or 5 h. Wireworm health was recorded for 70 or 126 d after exposure. Seeds were treated with the fungicides Dividend XLRTA (difenoconazole, mefenoxam) or Raxil MD (tebuconazole, metalaxyl), and/or the insecticides Vitavax Dual (lindane), Poncho 600F (clothianidin), Cruiser 350FS (thiamethoxam), Admire 240FS (imidacloprid), Gaucho 480FL (imidacloprid), Tefluthrin 20CS (tefluthrin), or Tefluthrin-Cruiser combinations. Most wireworms (> 80%) came into contact with the seeds in all treatments. Wireworms generally remained in contact throughout the observation period in the control treatments (Dividend, Raxil, untreated seeds). Unless moribund, wireworms were repelled after brief (< 20 min) contact in all Tefluthrin treatments. Most wireworms recovered from contact-induced morbidity within 21 d and did not relapse, except L. canus exposed to Cruiser and some A. obscurus exposed to Gaucho and Admire. Wireworm mortality was low (< 50%) in all treatments except L. canus exposed to Cruiser at 15 and 30 g a.i. 100 kg-1 seed (60 and 75%, respectively). Mortality was significantly less important when L. canus larvae were exposed to Tefluthrin-Cruiser combinations than when exposed to Cruiser alone. We suggest that efficacy assessments of insecticides for wireworm control require direct observation of their behaviour and long-term post-exposure health assessments, and discuss the impact of repellence and/or morbidity elicited by insecticides on wireworm control in the field.